Strengthening Pedestrian Safety: An Evaluation of Signals at Major Intersections in Lahore, Pakistan - Hina Saleemi; Zia ur Rehman; Saadia Tabassum; Ammad Hassan Khan; Abdur Rahim (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
Pedestrians’ safe mobility at intersections is associated with the facilities provided at the crossings. Lahore is one of the most populous cities in Pakistan. Too many road accidents occur daily at various areas of Lahore in which pedestrian-vehicle collision has a major ratio. To reduce the pedestrian-vehicle collisions, pedestrian signals are installed at major intersections of Lahore city. This paper examines the relationship between pedestrian signals and Level of Service (LOS), with a focus on enhancing awareness of pedestrian signal operation and investigates the impact of pedestrian signals on the LOS of intersections in Lahore in terms of pedestrian movement. Research shows that the poor level of awareness about how pedestrian signals work contributes to the inadequate level of service of intersections in terms of pedestrian movement. The results also provide valuable insights for policymakers and practitioners in developing effective strategies to improve the pedestrian experience and reduce pedestrian-vehicle collisions at intersections.